Young Children with ASD Use Lexical and Referential Information During On-line Sentence Processing - Bavin, Edith L.; Kidd, Evan; Prendergast, Luke A.; Baker, Emma K. (Frontiers in Psychology, 2016)
Research with adults and older children indicates that verb biases are strong influences on listeners’ interpretations when processing sentences, but they can be overruled. In this paper we ask two questions: (i) are children with ASD who are high functioning sensitive to verb biases like their same age typically developing peers?, and (ii) do young children with ASD and young children with typical development override strong verb biases to consider alternative interpretations of ambiguous sentences? Participants were aged 5-9 years (mean age 6.65 years): children with ASD who were high functioning and children with typical development. In task 1 biasing and neutral verbs were included (e.g., eat cake versus move cake). In task 2 the focus was on whether the prepositional phrase occurring with an instrument biasing verb (e.g. ‘chop the tree with the axe’) was interpreted as an instrument even if the named item was an implausible instrument (e.g. candle in ‘Cut the cake with the candle’). Overall, the results showed similarities between groups but the ASD group was generally slower. In task 1, both groups looked at the named object faster in the biasing than the non-biasing condition, and in the biasing condition the ASD group looked away from the target more quickly than the TD group. In task 2, both groups identified the target in the prepositional phrase. They were more likely to override the verb instrument bias and consider the alternative (modification) interpretation in the implausible condition (e.g., looking at the picture of a cake with a candle on it’). Our findings indicate that children of age 5 years and above can use context to override verb biases. Additionally, an important component of the sentence processing mechanism is largely intact for young children with ASD who are high functioning. Like children with typical development, they draw on verb semantics and plausibility in integrating information. However, they are likely to be slower in processing the language they hear. Based on previous findings of associations between processing speed and cognitive functioning, the implication is that their understanding will be negatively affected, as will their academic outcomes.